In Metastatic Non-small cell Lung Cancer Platinum-Based Treated Patients, Herbal Treatment Improves the Quality of Life. A Prospective Randomized Controlled Clinical Trial - Guo, Huiru; Liu, Jia X.; Li, Hegen; Baak, Jan P. A. (Frontiers in Pharmacology, 2017)
Background: According to clinical experience, Traditional Chinese Medicine (TCM) herbs added to platinum-based therapy (PBT) improve the Quality of Life (QOL) in metastatic non-small cell lung cancer (NSCLC) patients, but this must be prospectively validated. Patients and Methods: Based on clinical impressions regarding the effect of adding TCM herbs to platinum-based chemotherapy, we anticipated that 2 × 21 patients would be sufficient to obtain significant results with an α < 0.05 and power (1 - β) of 90%. To be on the safe side, we enrolled at least 28 patients in each group. In a prospective randomized controlled trial, 61 uniquely defined consecutive patients (PBT+PLACEBO, N = 32; PBT+TCM, N = 29) with stage IIIB-IV, Eastern Cooperative Oncology Group (ECOG) performance scores (PS) = 0–1 and TCM syndrome combined Qi-Yin deficiency were enrolled. These 61 patients were selected from originally 154 consecutive stage IIIB-IV lung cancer patients in the enrollment period. Patients were hospitalized and strictly controlled/surveyed during the entire 2-month treatment period, to guarantee use of or abstinence from TCM herbal and placebo fluids. Occurrence of nausea-vomiting, QOL by Functional Assessment of Cancer Therapy-Lung (FACT-L) scales and changes in ECOG “improved and stable rates” were compared before and after two treatment cycles. Results: Before treatment, the clinico-pathologic and QOL features in PBT+PLACEBO and PBT+TCM patients did not differ (P > 0.10). The only side effects attributed by some of the patients to the TCM herbs were transient, mild gastric/abdominal heaviness in the first 2 weeks, but these also occurred amongst the PBT+PLACEBO patients (17 and 13%, P > 0.10). The incidence rates of nausea during treatment were 17% in PBT+TCM versus 75% in PBT+PLACEBO; vomiting rates were 14 and 56% (P < 0.0001 and 0.002). Moreover, ECOG “improved and stable rates” were 90% in the PBT+TCM versus 69% in the PBT+PLACEBO group (P = 0.04). In PBT+TCM patients, FACT-L social/familial and functional subscales were better after 2 months’ treatment (P = 0.02 and 0.03). Contrarily, in PBT+PLACEBO patients, the QOL variables total score, physical and emotional subscales were worse after PBT treatment (P = 0.03, 0.0001, and 0.003). Conclusion: In stage IIIB-IV ECOG-PS = 0–1 NSCLC patients with Qi-Yin deficiency and platinum-based chemotherapy, adding TCM herbal medication improves the QOL. As this category of patients constitutes 40% of all metastatic NSCLCs, these results could have significant clinical impact.